Phytotechnology with biomass production sustainable management of contaminated sites - Erickson, L. E. (Larry Eugene), 1938-; Pidlisnyuk, Valentina V. (CRC Press, 2021)
"This book explains the concept of using phytotechnology with biomass production to improve soil quality and produce valuable products that have economic and social value. It is focused on the application of second generation biofuel crops to slightly contaminated or marginal post-military and post-mining soils. Based on recent research from the US, Ukraine, Germany, and Poland, along with studies from other countries, this is the first comprehensive book on using phytotechnology with biomass production at contaminated sites at a global level. It's also a great new resource for those who want to study and plan phytotechnology projects as well as those who carry them out"--